PENGGUNAAN PPT INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI HIMPUNAN - Sayyidah, Dahlia Rizki; Efriani, Arvin; Putri, Agustiany Dumeva (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
There are still many students who are afraid or even have difficulty understanding mathematics. One of them is the set material, this certainly influences the learning outcomes. Therefore, something interesting is needed to make students more interested and understand the material better. For this reason, researchers are interested in conducting research using interactive ppt with classpoints in the set material. The purpose of this research is to determine student learning outcomes before and after using interactive ppt. This type of research is an experiment with a one group pretest-posttest design. This research was carried out at SMP Negeri 17 Palembang in March 2024 involving class VII 6 students. The data collection technique used pretest and posttest. Data analysis uses hypothesis testing and homogeneity testing. The results of the hypothesis test obtained a value of 21 > 2.262, which means H0 is rejected and H1 is accepted. And the results of the homogeneity test are 1.446 < 3.178 which shows that the data the researcher has is homogeneous. The results of the research show that interactive ppt with classpoint can help students increase their enthusiasm for learning, be active, and improve their learning outcomes.